Comprehensive Investigation of Partitioned Thermal Barrier Coating: Impact on Thermal and Mechanical Stresses, and Performance Enhancement in Diesel Engines - Hüsna Topkaya; M. Quinn Brewster; Hüseyin Aydın (Applied Sciences)
The thermal barrier coating method is applied using materials with low thermal conductivity to increase the efficiency and improve the emissions of internal combustion engines. However, coated surfaces may be damaged due to the high thermal and pressure stresses encountered by the piston surface in the combustion chamber during engine operation. In this study, experiments and analysis were carried out for four piston models to analyze the coating layer and increase its strength: two partially coated piston surface models, a fully coated model, and an uncoated piston model. The results of the transient thermal analysis revealed that the fully coated piston model exhibited the highest surface temperature. Additionally, heat losses were observed to be lower in the fully coated model compared to the other piston models. Partially coated piston models exhibited lower heat flux on the coated surface but higher heat flux on the uncoated combustion chamber surfaces. Combustion analysis indicated that the fully coated piston model exhibited the highest in-cylinder temperature and pressure values, while the uncoated model had the lowest values. When comparing heat transfer rates on the walls, the uncoated piston model exhibited the highest transfer, whereas the fully coated piston model exhibited the lowest. Finally, the fully coated piston demonstrated the highest combustion efficiency.